THE YIELD AND FAT CONTENT OF OILY FLAX SEED DEPENDS ON BIOLOGICAL AND TECHNOLOGICAL FACTORS IN THE WESTERN FOREST STEPPE OF UKRAINE - Кучер, Ілля; Хоміна, Вероніка (SWorldJournal, 2023)
Aim. To establish the dependence of the yield and fat content in oil flax seeds on the variety, the seeding rate and the rate of application of the boron-containing drug. Results. A variety of oil flax more adapted to the conditions of the Western Forest-